Evaluation of Walking Street Market and Improvement Plans for Tourism Promotion. A Case Study of Thanon Pha Kram - PIM-AMORN, Niyomkar; NUTTHACHAI, Prongmanee (Journal of Environmental Management and Tourism; Vol 12 No 8 (2021): JEMT, Volume XII, Issue 8(56), Winter 2021, 2021)
This research evaluated the capacities and limitations of the walking street market named “Thanon Pha Kram” to help develop improvement plans for tourism industry promotion in Sakon Nakhon province. The capacities of the market were evaluated based on collected survey data using an accidental sampling method with 400 participants. The results indicated that overall, the street has sufficient room for good store arrangement, while the street community activities and management are well organized and safe. However, there were some barriers to ongoing tourism development such as parking area management, lack of public space, drainage system problems, and insufficient numbers of toilets and trash bins, as well as inappropriate scenery (installed canopies and overhead electricity poles). Based on the results and discussion, it was proposed that a designed area named “Ming Muang Court” should be developed as a new parking area, to increase the public space around the walking street. The clogged drainage system could be solved by increasing the number of trash bins together with using degradable packaging. This research suggested to use both permanent and temporary toilets to support the various types of tourists and to save on costs. The outcome of this research should be useful as a tool that can utilized for the effective management and evaluation of other walking streets.